Adjuvant radiotherapy and lymph node dissection in pancreatic cancer treated with surgery and chemotherapy. Issue 8 (3rd January 2014) - Mellon, Eric A.; Springett, Gregory M.; Hoffe, Sarah E.; Hodul, Pamela; Malafa, Mokenge P.; Meredith, Kenneth L.; Fulp, William J.; Zhao, Xiuhua; Shridhar, Ravi
<x xml:space="preserve">Abstract</x> BACKGROUND The objective of this study was to determine the effects of postoperative radiation therapy (PORT) and lymph node dissection (LND) on survival in patients with pancreatic cancer. METHODS The 2004 to 2008 Surveillance, Epidemiology, and End Results (SEER) database was analyzed to identify patients with pancreatic cancer who underwent surgery and received chemotherapy and to evaluate the correlation between overall survival (OS), PORT, and LND. RESULTS In total, 2966 patients were identified who underwent pancreatic resection (1842 PORT, 1124 no PORT). Median survival, 1‐year OS, and 3‐year OS were 21 months, 77%, and 28%, respectively, with PORT versus 20 months, 70%, and 25%, respectively, without PORT (P = .02). Subset analysis revealed that the benefit of PORT was limited to lymph node‐positive (N1) patients. Median survival, 1‐year OS, and 3‐year OS for patients with N1 disease were 19 months, 73%, and 25%, respectively, for those who received PORT versus 18 months, 67%, and 20%, respectively, for those who did not receive PORT (P < .01). An increasing lymph node count was associated with increased survival on multivariate analysis in all patients and in patients with N1 disease (both P < .001). Significant cutoff points for OS based on LND in patients with N1 disease were identified for those who had ≥8, ≥10, ≥12, ≥15, and ≥20 lymph nodes resected. Multivariate analysis for OS revealed that increasing age, T3 and T4 tumors, N1 stage, and moderately and poorly differentiated grade were prognostic for increased mortality, while female gender, PORT, and LND were prognostic for decreased mortality. In patients with N1 disease, other than patient age, all of these factors remained significant. In patients with N0 disease, only T1 and T2 tumor classification and having a tumor that was less than high grade were associated with survival benefit. CONCLUSIONS This SEER analysis demonstrated an associated survival benefit of PORT and LND in patients with N1, surgically resected pancreatic cancer who received chemotherapy. Cancer 2014;120:1171–1177. © 2013 American Cancer Society.